Otimização da eficiência energética no acionamento de motores de indução utilizando técnicas de controle adaptativo em tempo discreto - Scarmin, Alcir (2011)
This work approached the increased efficiency of induction motor drives using control techniques through a loss model and an adaptive structure. The review is presented with mainly energy efficiency controllers. Also, it are presented the electrical and mechanical models for motor control simulation with indirect field oriented (IFOC - Indirect Field Oriented Control) composed for speed, current and flux controllers. The identification of losses sources is used to development of efficiency controller with speed and flow. The methods of increasing energy efficiency of induction motor using a recursive search (SCSearch Control) and Loss-Model-based Controller (LMC) are presented, simulated and implemented. The SC is implemented with adaptive search step and the LMC by an optimal flux standard curve based on stator current. The SC converges to minimum input power, but it has slow response of 5s in transients. The LMC has quick response of 1s, but also it has dependency on parametric variation. Through the combination of SC and LMC, a Hybrid Adaptive Efficiency Controller (HAEC) is proposed. This controller has fast convergence of 1s in transitory and low sensibility with parameter variations. To implement the efficiency controllers, it was developed a platform composed by three-phase AC / CC / AC static converter with Space Vector Pulse Width Modulation controlled by a digital signal processor. Experimental results present an energy consumption reduction compared with constant flux drive of 29.7% for SC, 39.9% for LMC and 49.4% with HAEC. These results had shown the viability for HAEC project.